AKTIVITAS ENZIM PEROKSIDASE BAWANG MERAH YANG DIINTRODUKSI DENGAN BAKTERI ENDOFIT DAN TAHAN TERHADAP PENYAKIT HAWAR DAUN BAKTERI (XANTHOMONAS AXONOPODIS PV. ALLII) - Resti, Zurai; Habazar, Trimurti; Putra, Deddi Prima; ., Nasrum (Universitas Lampung, 2016)
Peroxidase enzyme activity of the introduced shallots with endophytic bacteria and resistant to bacterial leaf blightÂ (Xanthomonas axonopodis pv. allii). Bacterial leaf blight caused by Xanthomonas axonopodis pv. allii is an important disease in shallots. We have earned six isolates of endophytic bacteria, which have the ability to induce systemically resistance to shallots. One mechanism in induce resistance in plants is a change in the plant defense enzyme activity such as peroxidase. The purpose of this study was to calculate the peroxidase enzyme activity of shallots crop is being introduced with endophytic bacteria and is able to induce resistance to Xanthomonas axonopodis pv. allii. This research was conducted by introducing six isolates of endophytic bacteria on shallot bulbs and planted in greenhouse. Shallots crop that was 14 days old then inoculated with the bacterium Xanthomonas axonopodis pv. allii and incubated until symptoms appear. Peroxidase enzyme activity was calculated on the roots and leaves of shallots are 0, 1, 2, 4, 6, 8, 10, 15, and 30 days after inoculation (dai). The results showed an increase in the peroxidase enzyme activity of shallots crop is being introduced by endophytic bacteria compared to the control. Isolates ULG1E2 (Serratia marcescens PPM4) was isolate with the highest peroxidase enzyme activity both in the roots and leaves are 0,051 Ã¬m/ ml.